Expressed emotion as an assessment of family environment with mothers and fathers of 1-year-old children - Psychogiou, L; Netsi, E; Sethna, V; Ramchandani, P (2013)
Background: High levels of expressed emotion (EE) in parents have been found to put children at risk for emotional and behavioural problems. However, the majority of existing studies have focused on mothers of school-aged children and adolescents rather than younger children, and have only rarely included fathers. Methods: The present study examined the reliability of EE in mothers and fathers of 1-year old children. It also investigated whether depression and marital problems in the postnatal period predicted EE toward the child at 12 months. EE was assessed with the Preschool Five Minute Speech Sample in 163 families. Results: The rater-interrater and code-recode reliability was high for most EE dimensions. Mothers and fathers were found to display quite similar EE scores. Regression analyses showed that depression and couple relationship significantly predicted EE in mothers, but not fathers. Conclusions: The findings suggest that EE provides a reliable and useful assessment of the family environment in families of young children. © 2012 John Wiley and Sons Ltd.